2023
DOI: 10.1002/pssa.202300233
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Performance of PZT/PZ Composite Films Obtained by Sol–Gel Method

Abstract: PbZr0.52Ti0.48O3(PZT)/PbZrO3(PZ) composite films are deposited on LaNiO3/SiO2/Si substrates using sol–gel method, and annealed at 620 °C for a different time with the rapid thermal annealing technology. The microstructures, crystal structure, and electrical performance of the PZT/PZ composite films are researched. When the composite films are annealed at 620 °C for 3 min, the PZT films show the perovskite phase and the PZ films exhibit the pyrochlore phase with tiny perovskite phase, making the films obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…This is due to the presence of the amorphous phase in the film, which is a linear medium that will further reduce the P max of the thin film. Based on the above analysis, it has been found that the absence of hysteresis loops in the sample at the low-temperature annealing could be attributed to the presence of amorphous and pyrochlore phases in the PZ film, which have the degree of insulation and could resist external electric fields, resulting in linear hysteresis loops in the film under external electric fields, the similar phenomena are reported in the literature [16,26,42]. As shown in figures 5(c)-(d), the films annealed at 650 °C and 700 °C showed double P-E hysteresis loops of a high saturated polarization, which is the typical characteristic of antiferroelectric, and this is consistent with the microstructures and phase compositions.…”
Section: Dielectric Propertiessupporting
confidence: 77%
See 1 more Smart Citation
“…This is due to the presence of the amorphous phase in the film, which is a linear medium that will further reduce the P max of the thin film. Based on the above analysis, it has been found that the absence of hysteresis loops in the sample at the low-temperature annealing could be attributed to the presence of amorphous and pyrochlore phases in the PZ film, which have the degree of insulation and could resist external electric fields, resulting in linear hysteresis loops in the film under external electric fields, the similar phenomena are reported in the literature [16,26,42]. As shown in figures 5(c)-(d), the films annealed at 650 °C and 700 °C showed double P-E hysteresis loops of a high saturated polarization, which is the typical characteristic of antiferroelectric, and this is consistent with the microstructures and phase compositions.…”
Section: Dielectric Propertiessupporting
confidence: 77%
“…Therefore, if the annealing temperature exceeds 650 °C, the PZ film with perovskite structure undergoes the phase transition from antiferroelectric phase to ferroelectric phase under the action of the external electric field, which leads to the generation of double hysteresis loops in the PZ film. However, the low breakdown field strength causes energy loss during the field-induced phase transition, resulting in reduced energy storage efficiency and the inconspicuous antiferroelectric phase, the similar phenomena also occur in the literatures [16,42]. For energy storage applications, breakdown strength is a crucial factor to consider [45].…”
Section: Dielectric Propertiesmentioning
confidence: 75%
“…After fast thermal annealing at 620°C, a high energy storage density of 10.0 J/cm 3 was obtained in PbZr 0.52 Ti 0.48 O 3 (PZT)/PbZrO 3 (PZ) hybrid films on a LaNiO 3 /SiO 2 /Si substrate synthesized by sol-gel method . Rhun grown thick PZT films on platinum-coated silicon plates using sol-gel method, and move PZT films and ITO electrodes onto glass substrates (Yang et al, 2023). In visual range, the average amount of light that get through PZT stacks on glass was 70%, which makes it possible to make clear piezoelectric motors on glass for high-performance haptic devices and other new uses, like self-cleaning or making smart windows.…”
Section: Pzt Piezoelectric Filmsmentioning
confidence: 99%